Influence of Nanoclay on the Rheological Properties of PMMA/Organoclay Nanocomposites Prepared by Solvent Blending Technique. Issue 1 (July 2016) - Kumar, Manish; Kumar, Vijay; Muthuraja, A.; Senthilvelan, S.; Pugazhenthi, G.
Summary: The aim of present work is to study the effect of organoclay concentration on the rheological properties of poly(methyl methacrylate) (PMMA) nanocomposites. The PMMA nanocomposites containing organoclay in different proportions (3, 5 and 7 wt.%) were prepared by solvent blending method. The rheological properties of PMMA/organoclay nanocomposites were evaluated by parallel‐plate rheometer at fixed temperature (190 °C). Viscoelastic parameters such as storage modulus, loss modulus and complex viscosity exhibit the change from primarily viscous to elastic behaviour when the frequency increases. The thermal degradation kinetic model, Coats‐Redfern, also demonstrates the enhanced activation energy for the nanocomposites with an increase in the organoclay content.